Development of a diagnostic dna probe to detect setaria digtata: The causative parasite of cerebrospinal nematodiasis in goats,sheep and horses - Wijesundera, W.S.S.; Chandrasekharan, N.V.; Karunanayake, E.H.; Darmasena, S.P. (Elsevier, 1995)
Two repetitive sequences (IpSdM and IpSdS) have been cloned andsequenced from the genome of Setaria digitata. When IpSdM (214 bp) and IpSdS (201 bp) were aligned, a high degree of homology (85%) was observed, indicating that they belong to the same family of repeats. IpSdM represents a complete repeating element while IpSdS consists of two partial repeating elements arranged in tandem. The elements are present in about 10 000 copies comprising 2.8% of the S. digilata genome. As a diagnostic probe IpSdM detects as little as 100 pg DNA of both S. digilata and S. labiato-papillosa. It can also detect a single microfilaria and a L3 larva making it a valuable tool to monitor cattle and mosquito vector populations in the prevention of cerebrospinal nematodiasis.
Keywords: Setaria digilata; repetitive sequences; tandem repeats; DNA probes; cerebrospinal nematodiasis